Examining Rare and Low-Frequency Genetic Variants Previously Associated With Lone or Familial Forms of Atrial Fibrillation in an Electronic Medical Record System. (February 2015) - Weeke, Peter; Denny, Joshua C.; Basterache, Lisa; Shaffer, Christian; Bowton, Erica; Ingram, Christie; Darbar, Dawood; Roden, Dan M.
<x xml:space="preserve">Abstract</x> Background— Studies in individuals or small kindreds have implicated rare variants in 25 different genes in lone and familial atrial fibrillation (AF) using linkage and segregation analysis, functional characterization, and rarity in public databases. Here, we used a cohort of 20 204 patients of European or African ancestry with electronic medical records and exome chip data to compare the frequency of AF among carriers and noncarriers of these rare variants. Methods and Results— The exome chip included 19 of 115 rare variants, in 9 genes, previously associated with lone or familial AF. Using validated algorithms querying a combination of clinical notes, structured billing codes, ECG reports, and procedure codes, we identified 1056 AF cases (>18 years) and 19 148 non-AF controls (>50 years) with available genotype data on the Illumina HumanExome BeadChip v.1.0 in the Vanderbilt electronic medical record-linked DNA repository, BioVU. Known correlations between AF and common variants at 4q25 were replicated. None of the 19 variants previously associated with AF were over-represented among AF cases (P>0.1 for all), and the frequency of variant carriers among non-AF controls was >0.1% for 14 of 19. Repeat analyses using non-AF controls aged >60 (n=14 904), >70 (n=9670), and >80 (n=4729) years did not influence these findings. Conclusions— Rare variants previously implicated in lone or familial forms of AF present on the exome chip are detected at low frequencies in a general population but are not associated with AF. These findings emphasize the need for caution when ascribing variants as pathogenic or causative.